The diviners [compact disc, unabridged] - Bray, Libba (Bray, Libba. Diviners, 2012)
Seventeen-year-old Evie O'Neill has been exiled from her boring hometown and shipped off to the bustling streets of New York City. The only catch is that she has to live with her uncle Will and his unhealthy obsession with the occult. Evie worries her uncle will discover her dark secret: a supernatural power that has only brought her trouble. But when police find a murdered girl branded with a cryptic symbol and Will is called to the scene, Evie realizes her gift could help catch a serial killer.